ZAMANAGÓY DÁSTÚRLEW TILLERI JÁRDEMINDE MOBIL QOSÍMSHALAR JARATÍW METODIKASÍ - Qunnazarov, A.Q. (SCIENCE and SOCIETY, 2024)
This article describes the requirements for modern languages and types of programming, their world ranking, the creation of mobile applications in Python, Java programming languages, and the creation of mobile applications.
Keywords: modern programming languages; mobile learning; mobile applications; mobile technologies; mobile programming; SDK (Software Development Kit) API (Application Programming Interface) Android Studio; Kotlin; Java; JavaScript; Mobile Security